2021
DOI: 10.4491/eer.2021.158
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of carbofuran degradation by immobilized Bacillus sp. strain DT1

Abstract: The widespread application of carbofuran has raised increasing concerns about health damage and environmental pollution. To degrade carbofuran in liquid and soil media, Bacillus sp. strain DT1 was isolated from soil. The isolated bacterial strain used the compound as a sole source of carbon and energy. Using rice straw as a material for bacteria immobilization resulting in 97.5% of the insecticide was degraded in a biofilm-batch reactor at the 3rd cycle, which was about 20% higher than using glass slides for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In our previous report, Bacillus sp. DT1 isolated from soil showed effective degradation of carbofuran in liquid media and soil (Duc, 2022). In this study, the enhancement of carbofuran degradation in soil by augmentation with Bacillus sp.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…In our previous report, Bacillus sp. DT1 isolated from soil showed effective degradation of carbofuran in liquid media and soil (Duc, 2022). In this study, the enhancement of carbofuran degradation in soil by augmentation with Bacillus sp.…”
Section: Introductionmentioning
confidence: 68%
“…DT1 increased carbofuran degradation in soil (Duc, 2022). In this context, about 32.8 ± 6.0% carbofuran has remained in soil without herbicide history, and 19.7 ± 3.9% carbofuran has remained in soil with herbicide history (Duc, 2022). Similarly, Trabue et al (2001) showed that the increase in soil degradation of carbofuran was caused by repeated application of the pesticide.…”
Section: Carbofuran Degradation In Soilmentioning
confidence: 86%
See 2 more Smart Citations
“…Some studies report the biodegradation of insecticides, fungicides, and herbicides by green microalgae and cyanobacteria (see Avila et al, 2021; Encarnação et al, 2021; García‐Galán et al, 2020; Kalra et al, 2020). Regarding the biodegradation of the insecticide carbofuran, studies involving bacteria are predominant (Duc, 2022; Malhotra et al, 2021; Mishra et al, 2020; Mustapha et al, 2020), whereas there are no studies in the literature that report the bioremediation of carbofuran through microalgae. The use of these organisms has advantages because they are efficient, economically viable, and sustainable (Kalra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%